Dynamic Characteristic Improvement of Phase-Shift Full-Bridge Center-Tapped Converters Using a Model Predictive Control - Lee, Young Jae; Bak, Yeongsu; Lee, Kyo Beum (CENCON 2019 - 2019 IEEE Conference on Energy Conversion, 2019)
This paper proposes dynamic characteristic improvement of phase-shift full-bridge center-tapped (PSFB-CT) converter using a model predictive control (MPC). The PSFB-CT converters are used for a low voltage DC/DC converter (LDC) of electric vehicles (EVs). It usually controls the output voltage using a proportional-integral (PI) control. However, it has disadvantage in unsuitable dynamic characteristic. Additionally, the overshoot of the output voltage can be occurred in case the gain of the PI controller increases for improving the dynamic characteristic. Therefore, in this paper, the MPC method is proposed in order to improve the dynamic characteristic of the PSFB-CT converter without overshoot of the output voltage. In the proposed MPC method, the next state of the output power is predicted by the variation of the output power. It is calculated by the variation of output voltage and current of the PSFB-CT converter. As a result, the optimal phase-shift can be obtained. The effectiveness of proposed MPC method was proved by the simulation results.
Keywords: Dynamic characteristics; Electric Vehicles (EVs); Low voltages; Output power; Output voltages; Phase shift full bridges; PI Controller; Proportional-integral control; dynamic characteristic; low voltage DC/DC converter (LDC); model predictive control (MPC); phase-shift full-bridge center-tapped (PSFB-CT) converter